The effectiveness of promotional tools in enhancing awareness of MSCorp's products / Alfiee Qusyairi Abd Patah - Abd Patah, Alfiee Qusyairi (Faculty of Business and Management, 2007)
In general, promotion is the basic prominent in ensure each new firms penetrate market and keep sustaining growth for existing firms. However, after all this while, MSCorp had used almost all tools to promote their products to the public, but then, it still doesn't show any positive results. Without knowing where the weakness point, the objectives of promotions cannot be achieved or targeted. Thus, the study is undertaken to examine what are the pertinent factors that lead to the existing problem. The objective of this study is to determine the effectiveness of the limited promotional tools used by Malacca Stadium Corporation (MSCorp), to identify any association between promotional tools that customer gets familiar with the products with level of awareness among customers, to identify the association between promotional tools that customer gets familiar with the products with level of interest and desires among the customers towards the Mscorp's product, to identify the association between the promotional tools that customer gets familiar with the products with the action taken among the customers towards the Mscorp's product, and lastly to determine the promotional tools that the customer expects to raise their exposure towards MSCorp products.